THE USE OF NEW EDUCATIONAL TECHNOLOGIES IN THE TEACHING OF SPECIAL SCIENCES (Web of Teachers: Inderscience Research, 2025)
The use of new pedagogical technologies in the teaching of special disciplines is important to improve the quality of education, arouse the interest of students and the effective organization of the educational process. Below we briefly dwell on the basic data and modern methods used.